Recent Advances in Artificial Intelligence and Nanotechnology-Driven Strategies for Diagnosis and Therapy of Ocular Diseases - Kanugo, Abhishek; Teli, Nikeeta (Current Drug Delivery, 2025)
The eye is one of the primary structures of the body that allows perception of the entire world. A person’s activities rely entirely on having good vision, and any diseases or problems encountered with vision create a troublesome condition in life. Ocular delivery can potentially treat numerous eye-related disease conditions. The diseases that affect the eyes include glaucoma, dry eye syndrome, cataracts, conjunctivitis, diabetic retinopathy, keratitis, uveitis, Endophthalmitis, allergies, and others. The conventional dosage forms (eye drops, ointment) pose numerous challenges in treating ocular infections owing to their complex nature and several barriers. Recent advances in artificial intelligence and machine learning provide a preliminary diagnosis in the early stages of disease identification and are also useful during retinal surgery. The poor ocular penetration, low bioavailability, short retention time, and frequent administration are the limitations of conventional treatments. These limitations are easily solved with nanotechnology-driven approaches. The current state-of-the-art review explores eye physiology, barriers (precorneal, corneal epithelium, lacrimal sac, blood-ocular, and efflux protein), limitations of the conventional and nanotechnology-based delivery (Lipid-based, polymer-based, metal and inorganic NPs, vesicle-based NPs, and miscellaneous). These nanocarriers facilitate good permeation, extended retention time, augment solubility, improve bioavailability, improve patient comfort and compliance, and minimize dosage application. The nanocarriers are equally effective in treating the anterior and posterior regions of the eyes, whereas conventional ones have failed to treat them effectively. The recently approved agents and patents are elaborated on ocular drug delivery. Advancements in stem cell and gene therapy are also gaining attention for treating inherited and acquired retinal diseases.
Keywords: hydrogels